Perbandingan Pengaruh Teknik Meneran Tiup-Tiup dan Valsava terhadap Derajat Ruptur Perineum Pada persalinan di PMB Kabupaten Kampar Tahun 2024 - Amir Luthfi; Nina Khairun Nisha; Dhini Anggraini Dhilon (Jurnal Ners, 2025)
Incorrect pushing during the second stage of labor can cause perineal rupture. Perineal rupture is the second cause of postpartum hemorrhage after uterine atony The purpose of this study was to analyze the comparison of the effect of the inflatable technique and the Valsava technique on the degree of perineal rupture in childbirth during stage II at PMB Kampar Regency in 2024. This type of research is Quasi Experimental Design with posttest only control group design. This study was conducted on August 26 - October 17, 2024 with a total sample of 20 vaginal delivery women, 10 laboring women applying the inflatable technique and 10 laboring women using the valsava technique. The data collection method used accidental sampling technique and data collection using observation sheet. There were 6 respondents (60%) who applied the inflatable technique with degree 0 (no rupture) with a mean of 0.50, while in the valsalva technique there were 7 respondents (70%) with degree 2 perineal rupture with a mean of 1.70 and bivariate analysis with the Mann-Whitney test showed the results of Asymp. Sig. (2-tailed) value p = 0.002 ≤ 0.05.